Single-Cell RNA-Sequencing Portraying Functional Diversity and Clinical Implications of IFI6 in Ovarian Cancer - Zhao, Hongyu; Li, Zhefeng; Gao, Yan; Li, Jie; Zhao, Xiaoting; Yue, Wentao (Frontiers in Cell and Developmental Biology, 2021)
Ovarian cancer (OC) is one of the most lethal gynecologic malignancy. Most patients finally died of metastasis, due to a lack of other treatments aimed at improving the prognosis of OC patients. In present study, we use multiple methods to identify prognostic S1 is regarded as the dominant subtype in OC, possessing most ligand-receptor pairs with other cells types. Based on markers of S1, the consensus clustering algorithm is used to explore the clinical treatment subtype in OC. As a result, we identify two clusters associated with distinct survival and drug response. Notably, IFI6 contributes to the cluster classifications and is seemed as a vital gene in OC carcinogenesis. Functional enrichment analysis demonstrates its functions involved in G2M and cisplatin-resistance, downregulation of IFI6 suppresses proliferation capabilities and significantly potentiates cisplatin-induced apoptosis of OC cells in vitro. To explore the possible mechanisms of IFI6 influencing OC proliferation and cisplatin-resistance, GSEA is conducted and shows that IFI6 is positively correlated with NFKB pathway, which is validated by RT-qPCR. Significantly, we develop a prognostic model including IFI6, RiskScore, which is an independent prognostic factor and presents encouraging prognostic value. Our findings provide novel insights into elucidating the biology of OC based on single-cell RNA-sequencing. Moreover, this approach is potentially helpful for personalized anti-cancer strategies and predicting outcomes in the setting of OC.